A study of some morphological characteristics of some fig cultivars spread in some locations of Latakia Governorate - مخول جرجس; زهرة رنا (Latakia University Journal -Biological Sciences Series, 2021)
This research was conducted during the period of 2019-2020 to study the morphological characterization of some fig cultivars spread in two locations different in their high above sea level (100-300m). As 14 cultivars were determined for the purpose of morphological characterization and for determination of the degree of morphological relationship, in addition to set the morphological identity for fig cultivars of each location. The morphological analysis was done based on 14 morphology characteristics (leaves, inflorescences) for each location. The morphological tree for fig cultivars in AL-Kaloof location showed two main groups with a contrast ratio of (63%). The first group included three cultivars (K1, K3, K4) with a contrast ratio of (51%) approximately between (K1) cultivar and (K3, K4) cultivars while the contrast ratio was 0% between (K3) and (K4) cultivars. The second group included four cultivars (K2, K5, K6, K7) with a contrast ratio of (38%). While the morphological tree for fig cultivars in Wadi AL-Ramim location showed a contrast ratio of (69%) between (R7) cultivar and (R1, R2, R3, R4, R5, R6) cultivars. The degree of morphological similarity is contrastive among the studied cultivars, and the percentage of contrast among Wadi AL-Ramim cultivars is higher than AL-Kaloof cultivars.